STUDENT’S GRAMMAR MASTER OF SIMPLE PRESENT TENSE BY USING EGRA EXPOSURE, GENERALIZATION, REINFORCEMENT, AND APPLICATION METHOD AT SENIOR HIGHT SCHOOL MUHAMMADIYAH JAYAPURA - Yanti Diana (Indonesian Journal of Education (INJOE), 2022)
Nowadays English send to be the crucial language in the word. The existence of English subject should be focus on the grammar.Because grammar stated as the complication thing in English. This study focused on simple present tense, teaching English subject especially in simple present tense generally make students felt bored because they did not feel confidence and felt difficult in understanding the material Here, EGRA method to be alternative of the problem in which the EGRA method can make students more enthusiastically in learning and confident in simple present tense. EGRA is an acronym of four major learning styles for student’s confidence and confidence, namely Exposure, Generalization, Reinforcement, and Application. Many researcher found that teaching by using EGRA method give well understanding for students in learning a new language. It can be shown that students become more creative, active and communicative in the class. The success of learning also depend on the method use by the teacher. Here the EGRA method used tofulfil the needed of students